2002
DOI: 10.1002/jbm.10351
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemical behavior of Ti‐6Al‐7Nb alloy with and without plasma‐sprayed hydroxyapatite coating in Hank's solution

Abstract: The electrochemical behavior of Ti-6Al-7Nb alloy with and without plasma-sprayed hydroxyapatite (HA) coating was investigated in Hank's balanced salt solution at 37 degrees C. This behavior was evaluated by analyzing both corrosion potential variation with time curves and potentiodynamic polarization curves. The polarization curves were determined both in aerated and deaerated solutions. It was found that the corrosion potential of uncoated sample is always more noble than that of coated one. In aerated soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 11 publications
0
24
0
3
Order By: Relevance
“…This result is also supported by the very low corrosion current density at the corrosion potential (order of nA/cm 2 ), showing that this does not compromise the corrosion performance of the Ti alloy under service conditions. On the other hand, thick and porous layers on implant materials have been related to good osteointegration ability [2,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This result is also supported by the very low corrosion current density at the corrosion potential (order of nA/cm 2 ), showing that this does not compromise the corrosion performance of the Ti alloy under service conditions. On the other hand, thick and porous layers on implant materials have been related to good osteointegration ability [2,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon indicates the thickening of the passive oxide film. 25 There is no markedly fluctuation in the curves of pure Zr, pure Ti, and LM106 till the end of the experiment, but LM1 and LM1b show several peaks before the steady state is achieved. In addition, LM1b shows the highest OCP values compared with other alloys in both electrolytes.…”
Section: Corrosion Behaviormentioning
confidence: 91%
“…For example, Wataha et al 19 reported the cytotoxicity effects on three In this study, we attempt to address the question by using various electrochemical measurements to reveal the corrosion performance and ion release behaviors of the Zrbased BMGs; furthermore, we implemented, in vitro cytotoxicity evaluation by using two cell lines (L929 and NIH3T3) to evaluate their in vitro biocompatibility. 25 (in at %), also known as LM106, LM1, and LM1b, respectively, were fabricated by Liquidmetal Technologies (Lake Forest, CA). Briefly, the alloy ingots were prepared by arc melting method with high purity metals Zr (99.8 wt %), Ti (99.8 wt %), Nb (99.7 wt %), Cu (99.95%), Ni (99.98 wt %), Be (99.9 wt %), and Al (99.99 wt %) in an argon atmosphere, and then the ingots were inductively remelted in a crucible and cylindrical bulk amorphous samples of 5 mm diameter were obtained by injection casting into a copper mould.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion potential in these curves is defined by the intersection of the activation polarization anodic curve related to the formation of the passive film with the activation cathodic curve of oxygen reduction. This intersection takes place at potentials lower than where there is already a well-formed passive film on the surface [9]. Corrosion current density, to which the corrosion rate is normally proportional, is an important parameter for evaluating the kinetics of corrosion reactions.…”
Section: Potentiodynamic Polarization Testsmentioning
confidence: 99%